Nanoethics and nanotoxicology - Houdy, P. (Philippe); Lahmani, M. (Marcel); Marano, F. (Francelyne) (Heidelberg, Germany Springer Berlin, 2011)
This is a fast developing field of research and application in many domains such as in medicine, pharmacy, cosmetics and agro-industry. The book addresses the lastest fundamental results on nanotoxicology and nanoethics, and the enormous range of potential applications in the fields of medical diagnostics, nanomedicine, and food and water administration. Nanoscale objects have properties leading to specific kinds of behaviour, sometimes exacerbating their chemical reactivity, physical behaviour, or potential to penetrate deeply within living organisms. Hence it is important to ensure the responsible and safe development of nanomaterials and nanotechnologies. This fourth volume in the Nanoscience series should make its mark, by presenting the state of the art in the fields of nanotoxicology and nanoethics. This is the first book to combine both scientific knowledge and ethical and social recommendations. It also presents specific policies on nanotechnologies set up by national and international authorities. This book is of interest to engineers, researchers, and graduate students
Management in the workplace --  Health protection --  Part B: Experimental toxicology of nanoparticles and their impact on the environment -- surface reactivity of manufactured nanoparticles -- nanoparticle transfer -- ecotoxicology: reactivity in living systems -- toxicological models -- life cycle models -- nanoethics -- nano-ethics: challenges and opportunities -- philosophical guidelines for the responsible use of nanotechnology -- ethics and regulation -- the situation in france -- the situation in europe and the rest of the world -- nanotechnology and the law -- social issues -- labour relations -- risk perception -- robotics, ethics, and nanotechnology -- ethics and industrial production
Electronic reproduction.
Keywords: Nanoscience -- Moral and ethical aspects; Toxicology; Nanotechnology -- Moral and ethical aspects